Triclinic Pedial Sarcosinium Hydrogen l(+)‐Tartrate—Crystal Growth, Pyroelectricity, Thermal Expansion, and Linear Optical Properties. Issue 2 (11th June 2019) - Bohatý, Ladislav; Bayarjargal, Lkhamsuren; Andersen, Lionel; Held, Peter; Becker, Petra
Abstract: Single crystals of optical quality and dimensions up to 25 × 25 × 40 mm 3 of sarcosinium hydrogen l (+)‐tartrate and up to 15 × 20 × 30 mm 3 of sarcosinium hydrogen d (−)‐tartrate are grown from aqueous solution during growth periods of 10–14 weeks. For sarcosinium hydrogen l (+)‐tartrate refractive indices and their dispersion in the wavelength range 365–1083 nm are determined. The biaxial positive crystals show marked optical anisotropy with maximum birefringence at 365 nm of Δ n = 0.089 and only small orientation dispersion of the principal axes of the optical indicatrix. Based on the linear optical data, phase matching conditions for collinear second harmonic generation (SHG) are analyzed. The optical properties allow SHG phase matching for both, type I and type II processes. Temperature‐dependent coefficients of the tensor of thermal expansion [ αij ] between 145 and 300 K show pronounced anisotropy and moderate orientation dispersion of thermal expansion, with principal values at 293 K of α 11 0 = −3.3(1) × 10 −6 K −1, α 22 0 = 35.7(1) × 10 −6 K −1, and α 33 0 = 66.6(1) × 10 −6 K −1 . The absolute value of the pyroelectric vector | p σ | of sarcosinium hydrogen l (+)‐tartrate amounts to about 20 µC K −1 m −2 and varies only slightly with temperature in the temperature range 100–320 K. Abstract : Crystals of triclinic pedial sarcosinium hydrogen l (+)‐tartrate possess no symmetry besides translation symmetry. Hence, anisotropy of macroscopic crystal properties is not restricted by symmetry and therefore possesses the maximum degree of freedom. Using grown large single crystals, the full anisotropy of thermal expansion [ α ij ], pyroelectric vector p and respective temperature dependences, and linear optical properties including wavelength dispersion are studied.